Respon Bawang Merah (Allium ascalonicum L) Terhadap Pemotongan Umbi dan Aplikasi Pupuk Organik - Laila Nazirah; Dwi Indahwan Libra (Agrium, 2019)
Shallots is a horticultural commodity that has high economic value. One way to improve the growth and yield shallots is by cutting the tubers and providing it with chicken manure. This research was conducted in Paloh Lada Village which is located in Dewantara Sub-district, North Aceh Regency and Agroecotechnology Laboratory at the Faculty of Agriculture, Malikussaleh University starting from September-November 2018 with the aim to determine the effect the size the tuber cuts and the adduction chicken manure doses to Bima Brebes shallots growth and yield. This research uses a Randomized Block Design with Factorial pattern. The first factor is the size of the tuber cuts which consists of three levels, namely level 0 (without cutting), cutting 1/4 part of the tuber and the last one is cutting 1/3 part of the tuber. The second factor is the dose of the chicken manure which also consists of 3 levels, namely dose 0 (without chicken manure), 75 grams of chicken manure/polybag and 100 grams of chicken manure/polybag. This research consists of 9 treatment combinations 3 replications and 27 experimental units. The results of this research shows that the tuber cutting significantly affected the number of leaves at 14 days after planting, then it has a very significant effect on the number of leaves at 42 days after planting and it has an effect on the tuber dry weight. Meanwhile, the tuber cutting has no significat effect on the plant height, number of tillers, tuber gross weight and tuber weight loss. The adduction of chicken manure significantly affected the plant height at 28 days after planting and the tuber dry weight, although it doesn’t have any significant effect on the plant height at 14 and 42 days after planting, number of leaves, number of tillers, tuber gross weight and tuber weight loss.